OP61 Areas of Covid-19 prevalence: drivers of prevalence and mitigating strategies. (26th August 2022) - Lewis, Catherine; Johnson, Sheena; Hartwig, Angelique; Ubido, Janet; Coleman, Anna; Gartland, Nicola; Armitage, Chris; Fishwick, David; Tongeren, Martie Van
Abstract : Background: UK local authorities that experience high sustained levels of COVID-19 prevalence are termed areas of enduring prevalence (AEP) according to SAGE (2021). A study was carried out as part of the PROTECT National Core Study on Transmission and Environment, to investigate reasons for sustained high prevalence, along with mitigation strategies employed by Directors of Public Health (DsPH). Methods: Interviews were conducted with DsPH in 19 local authority areas across England, between July and October 2021. This included nine areas identified as AEP and ten comparison areas (CA), including statistical neighbours of the AEP (PHE, 2019) that had not experienced enduring prevalence. DsPH were asked about factors contributing to enduring prevalence, along with mitigating strategies employed during the pandemic. Results: Participants identified various factors associated with enduring prevalence, including high deprivation levels, overcrowded housing, and low vaccination rates. Deprivation and employment were often jointly discussed as creating major barriers for people to be able to sef-isolate or work remotely. Not receiving sick pay, working on zero-hours contracts or in insecure employment were associated with inability to self-isolate. There were strong similarities in the drivers of enduring prevalence described by DsPH in the AEP and CA. All participants asserted that there were differences in these drivers between wards or geographical areas within their local authority area, and between different groups of people, including people from different and age groups and ethnic backgrounds. Participants in the AEP were more likely to discuss the impact of structural factors such as deprivation or work insecurity. All DsPH implemented a variety of effective mitigation strategies over the course of the pandemic, including local contact tracing, local testing and vaccination efforts, isolation support, communication campaigns, engagement with business and education, and community engagement. Conclusion: The research shows that deprivation, employment and housing, along with vaccination rates, are key drivers of COVID-19 prevalence. Work related factors such as insecurity and absence of sick pay may influence behaviours and increase the risk of virus transmission. DsPH advised that more research is needed on the factors that drive prevalence, on the effectiveness of mitigation strategies, and on the long-term impacts of the pandemic, including the impact on health inequalities and on the wider system for recovery.